The qur'an or the bible which is God's word - Sheikh Ahmed Deedat; Shorrosh, Anis; Saba Islamic Media ([Kuala Lumpur] : Saba Islamic Media)
This is a great debate between Sheikh Ahmed Deedat and Dr. Anis Shorrosh in August 1988, at the National Exhibition Center, Birmingham, England
Title from container
Speakers: Sheikh Ahmed Deedat, Dr. Anis Shorrosh
VCD format
Keywords: Koran; Bible; Islam -- Relations -- Christianity